EFFECT OF ORGANIC MATTER AND SOIL SUSPENSION ON CLOGGING DRIP EMITTERS UNDER APPLICATION TWO DIFFERENT WATER QUALITIES - ABDULLAH , ZERAVAN A.; KHALAF, AKRAM A. (Journal of Duhok University, 2022)
One of the most critical variables affecting the performance of drip irrigation systems is emitter clogging, which occurs quickly as a result of irrigation systems operating under insufficient pressure or due to poor water quality, not only affecting water distribution uniformity but also results in insufficient irrigation. To investigate the clogging potential of the drippers, two types of water quality were tested. Using local materials organic matter and soil suspension account for more than 47 percent of the clay content was applied with water. The tests identified the clogging severity of emitters with organic matter application for both water qualities Sumael (LSI) and Bazalan (LSII) respectively. In general, clogging ratios developed with time for both water qualities, the most distinct was organic matter application that reduced the discharge rate to 15.561% for Sumael water (LSI) corresponding to Bazalan water (LSII) was 38.002%. The flow rate of the drippers was also affected by the soil suspension particles. The percentages found in the Bazalan water was 5.62%, which was close to 5.575% in the Sumael water.